ANALISIS PROSES BISNIS USAHA MIKRO KECIL MENENGAH (UMKM) KONVEKSI RYAN COLLECTION DI KABUPATAN KUDUS - Widayanto Widayanto (Universitas Diponegoro, 2017)
Business process management is an abstraction that describes the way people or parties interact within the system, to handle business requests which are described in a particular way. In the business process the company is able to manage each field in it so that the company is able to achieve the goals that have been planned previously. Business processes include the production and manufacturing process in producing goods or services, and then these are marketed as means to market the products. Furthermore, management in terms of finance as a source of funds for financing the production process should also be prepared in order to keep the production of goods maintained properly. In addition, financial management is also intended to pay human resources workers who work on the existing production processes. One of the purpose of business process analysis is to analyze business processes that exist in business organizations related to the use of firm’s resources. Hence, the use of business organization resources can be generated by to be more effective and efficient by business processes analysis. Riyan Collection, an SME in convection industry, does not have well-structured business organization. The operation and production are controlled by the sole owner, so there is no standard procedure to utilize the existing business processes. The purpose of this research is to arrange the Riyan Collection’s organizational structure and to organize the business process model. This research has developed Riyan Collection’s organization structure and the model of business process. This research also suggests the firm to design a computer-based information system to support the management in making decisions..